2019
DOI: 10.1161/jaha.118.011130
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Beta and C‐Terminal Fibroblast Growth Factor 23 in Patients With Chronic Heart Failure and Chronic Kidney Disease

Abstract: BackgroundIn patients with chronic heart failure and chronic kidney disease, correction of anemia with erythropoietin‐stimulating agents targeting normal hemoglobin levels is associated with an increased risk of cardiovascular morbidity and mortality. Emerging data suggest a direct effect of erythropoietin on fibroblast growth factor 23 (FGF23), elevated levels of which have been associated with adverse outcomes. We investigate effects of erythropoietin‐stimulating agents in patients with both chronic heart fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Generally, endogenous EPO levels are elevated during early-stage CKD (94), exogenous EPO is typically administered to patients with late-stage CKD due to the presence of renal anemia, and FGF23 cleavage may decrease as renal function declines (95,96). iFGF23 is considered the bioactive form, and high cFGF23 expression is associated with poor prognosis in patients with CKD (17,69). Future studies are required to determine the biological activities of the C-terminal fragments of FGF23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, endogenous EPO levels are elevated during early-stage CKD (94), exogenous EPO is typically administered to patients with late-stage CKD due to the presence of renal anemia, and FGF23 cleavage may decrease as renal function declines (95,96). iFGF23 is considered the bioactive form, and high cFGF23 expression is associated with poor prognosis in patients with CKD (17,69). Future studies are required to determine the biological activities of the C-terminal fragments of FGF23.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these observed effects were independent of iron status. Studies on patients with chronic heart failure and CKD have reported that exogenous EPO injections markedly increase cFGF23 expression (69,70). The potential reasons for these differences may be attributed to the differences in renal functions of patients and/or the dose of rhEPO used.…”
Section: Fgf23 and Epomentioning
confidence: 99%
“…100 In the Mechanisms of Erythropoietin Action in the Cardiorenal Syndrome (EPOCARES) study in patients with CRAS, epoetin-b for 50 weeks led to significant increases in Hb and hematocrit levels compared with standard care. 101 However, significant increases in C-terminal fibroblast growth factor 23 were also observed with epoetin-b therapy, which were positively associated with an increased risk of mortality, providing a possible mechanism for the increased CV risk. 101 Consistent with the limited data regarding the use of ESAs in patients with CRAS, and lack of recommendation for their use in HF, 79 real-world data suggest that a relatively low proportion of patients with CRAS (10%) are prescribed ESA therapy, with previous iron therapy and more severe CKD being predictors of initiating ESA therapy.…”
Section: Erythropoiesis-stimulating Agentsmentioning
confidence: 99%
“…However, in CKD, where FGF23 cleavage is impaired, iron deficiency, ESAs, and inflammation increase iFGF23. The relative amounts of circulating iFGF23 and cFGF23 are impacted not only by iron status, inflammation, ESA use, and the presence of CKD, but also by the iron formulation administered (Table 4 [90][91][92][93][94][95][96][97] ). Indeed, certain i.v.…”
Section: Risks Of Iron Administration In Ckdmentioning
confidence: 99%